Contribution of limbic norepinephrine to cannabinoid-induced aversion - Carvalho, Ana Raquel Franky Gomes (2010)
RATIONALE: The cannabinoid system has risen to the forefront in the development of novel treatments for a number of pathophysiological processes. However, significant side effects have been observed in clinical trials raising concerns regarding the potential clinical utility of cannabinoid-based agents. Understanding the neural circuits and neurochemical substrates impacted by cannabinoids will provide a better means of gaging their actions within the central nervous system that may contribute to the expression of unwanted side effects. OBJECTIVES: In the present study, we investigated whether norepinephrine (NE) in the limbic forebrain is a critical determinant of cannabinoid receptor agonist-induced aversion and anxiety in rats. METHODS: An immunotoxin lesion approach was combined with behavioral analysis using a place conditioning paradigm and the elevated zero maze. RESULTS: Our results show that the non-selective CB1/CB2 receptor agonist, WIN 55,212-2, produced a significant place aversion in rats. Further, NE in the nucleus accumbens was critical for WIN 55,212-2-induced aversion but did not affect anxiety-like behaviors. Depletion of NE from the bed nucleus of the stria terminalis was ineffective in altering WIN 55,212-2-induced aversion and anxiety. CONCLUSIONS: These results indicate that limbic, specifically accumbal, NE is required for cannabinoid-induced aversion but is not essential to cannabinoid-induced anxiety.